Meniscus Guide Slot-Die Coating For Roll-to-Roll Perovskite Solar Cells. (30th January 2019) - Burkitt, Daniel; Greenwood, Peter; Hooper, Katherine; Richards, David; Stoichkov, Vasil; Beynon, David; Jewell, Eifion; Watson, Trystan
Abstract: Roll-to-roll slot-die coating with a meniscus guide is used to deposit several layers in a P-I-N perovskite solar cell stack, including the perovskite layer. The use of various length meniscus guides as part of the slot-die head allows controlled coating of these layers at a common coating speed. The length of meniscus guide used is optimised and related to the rheology of the coated ink and appropriate choice of meniscus guide length provides a way to avoid flooding of the coated area and improve coating definition. Initial coating trial results suggest the low-flow limit of slot-die coating is still applicable when using a meniscus guide, which is an important and previously unreported observation, application of this theory to meniscus guide coating provides a useful tool for rapidly determining the appropriate coating conditions that can be used as part of a manufacturing process. This is further explored through the deposition of perovskite solar cells by roll-to-roll slot-die coating. The perovskite layer is deposited using a sequential slot-die deposition process using a low toxicity dimethyl sulfoxide ink for the lead iodide layer, it is found that increasing the drying oven temperature and air flow rate can be used to improve the uniformity of the layer but this can also result in deformation of the plastic substrate. Functioning perovskite solar cells are demonstrated using this technique, but a large variation is found between device performances which is attributed to the poor uniformity of the perovskite layer and damage caused to the substrate by excessive heating.